The Sites of Transcription and Translation for Euglena Chloroplastic Aminoacyl-tRNA Synthetases - Hecker, L. I. (1974)
We find that cycloheximide completely blocks the light-induced apearance of Euglena chloroplastic aminoacyl-tRNA synthetases in dark-grown cells of Euglena gracilis var. bacillaris. Streptomycin, on the other hand, has no effect on the light-induction of these organellar enzymes. These observations, together with the finding that an aplastidic mutant (strain W(3)BUL, which has neither significant plastid structure nor detectable chloroplast DNA) contains low levels of the chloroplastic synthetases, indicate that the chloroplastic synthetases are transcriptional products of nuclear genes and are translated on cytoplasmic ribosomes prior to compartmentalization within the chloroplasts.